COMMUNITY SERVICE, EDUCATION ON PREMATURE INFANT CARE AND EARLY DETECTION OF HIGH RISK MOTHERS AND CHILDREN THROUGH A KARO CULTURAL APPROACH IN MEDAN TUNTUNGAN DISTRICT - Herlina; Leni Agustina; Widia Astuti Tanjung (Cattleya Darmaya Fortuna, 2024)
The infant mortality rate caused by complications of premature birth is still a serious health challenge in the Medan Tuntungan area. Cultural factors and a lack of understanding of the danger signs of premature babies often lead to delays in medical treatment. This community service activity aims to improve the knowledge and skills of mothers and families in the care of premature babies and early detection of high risk mothers and children through the local wisdom approach of Karo Culture. The program was held on November 15, 2024 with interactive counseling methods, premature baby care demonstrations, and group discussions. The results of the evaluation showed a significant increase in participants' understanding of safe premature infant care procedures and the importance of early detection. Culture-based approaches have proven to be effective in minimizing communication barriers between medical personnel and the community, thereby increasing family trust and awareness in following modern medical standards.